Polemical Discourse on Ḥadīth Matn Analysis in Southern Nigeria - Waliyullahi, Adeyemi Adeola; Teslim, Akinwale Adelodun (KWASU Journal of Religious Studies, 2018)
Misconceptions about interpretation of prophetic traditions have been claimed to have precipitated uncompromising controversies and rejoinders among Muslim scholars in the past and present time, especially in the contemporary Southern Nigeria. It all began as a result of different perceptions deduced by the Muḥaddithūn (Traditionists) regarding the verbal reports, deeds and tacit approval of the Prophet. This research paper has examined preservation of Ḥadith from the Prophetic era till the period of the Tābi‘ūn, the roles played by the Muslim scholars in Nigeria to shed light on the misconstrued Aḥādīth. Historical and analytical methods were adopted in the study to pinpoint the genesis of Ḥadith misconceptions, polemics on selected issues that sprouted up in the recent time, as well as rudiments of proffering solutions to the misconstruction of Ḥadith Matn. The finding has revealed that some Muslim scholars were benighted of in-depth cognition of Ḥadith contents. However, Muslims need to take recourse to unbiased Ḥadīth commentaries in order to curtail their intra-religious rivalries regardless of their doctrinal differences.